Pemanfaatan Learning Manegement System Berbasis Google Classroom Dalam Pembelajaran Ips Di Sekolah Dasar - Putra, Lovandri Dwanda; Alfinda, Risa; Sakinah, Syarifah; Arriant, Yusuf (LPPM Universitas Muhammadiyah Sumatera Barat, 2024)
AbstracThe information and technology industries are undergoing rapid change right now. In this day and age, there are many new options, and technology has made it possible to use e-learning, which is a variety of learning methods used in schools. E-Learning is an instructing and educational experience that is upheld and created through innovation and computerized media, and is likewise a type of the distance learning idea. The purpose of learning media is to show objects that students cannot directly see. A teacher needs to be able to select media that best illustrate the idea being taught. The world of education, as well as online learning and what are referred to as online classes, is impacted by the latest technological advancements. Several companies, including Google, have developed online learning extensively using Google Classroom. Google Homeroom is an application that makes it conceivable to make study halls in the internet. It is anticipated that using the Google Classroom-based E-Learning application for social studies instruction will make it simpler for educators to archive and organize assignment files as well as the assessment procedure. Learning management systems (LMS) can simplify learning, provide unlimited access to learning at any time, from any location, and make it easier for educational institutions to improve the learning process. The utilization of LMS can likewise make learning more adaptable in concentrate on time with the goal that it can make understudies more free. Through the LMS, teachers can also link student activities in detail. Using LMS or a combination of LMS-based learning models has been shown to increase activity, learning outcomes, and motivation in the